การสืบทอดสื่อพื้นบ้านเท่งตุ๊ก จ.จันทบุรีเพื่อเสริมสร้างความเข้มแข็งให้แก่ชุมชน - สุชาดา พงศ์กิตติวิบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research are to study the process of Teng Tuk inheritance which has been changed according to the context of the community, the effect of the outsiders on Teng Tuk inheritance, contributing and inhibiting factors in the process and the role of Teng Tuk to the community. The instruments used in this study are the document analysis, in-depth interview, focus group interview and participatory and non-participatory observations. The subject participants in this study are groups of Chao lao artists, the community leaders, Chao lao people and the audiences both inside and outside the community. The results are as follows: (1) The researcher regarded as the external factor has the effect on the reinforcement of folk media inheritance and the reconciliation of the cultural groups in Chao lao. (2)The context of the community would be the contributing or the inhibiting factor depending on power relations between the artists and the external factors. (3) The Project of Folk Media for Health regarded as the outsider has the role to increase the capital of Teng Tuk inheritance by the proactive cultural process. (4) The impact of external factor on the community change has influenced Teng Tuk inheritance in the case of some adjustments; for example, organizational structure, newcomers recruitment, motivation for joining the groups, teaching method, meaning, artists, messages, channels, receivers, capital, and participation. (5) The external factors have caused the separate of Teng Tuk culture which included people or artists, department or organization, production process, role, and audiences’ s taste (6) The role of Teng Tuk is considered as a dynamic along with the context of community and the strength of itself. The important role is the role that could not be replaced by mass media; for example, being the spiritual supporter, and the reconciliation of community. The most significant role was to strengthen the community’s identity to encounter with the external culture